Posouzení informačního systému firmy a návrh změn - Placzková, Monika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce, se zabývá posouzením současného informačního systému ve firmě, která si nepřeje zveřejnit své obchodní jméno. Bude označována jako ČTKH. Posouzení současného informačního systému firmy bude vycházet z výsledků dvou dotazníků. Výstupem průzkumů bude zhodnocení současného informačního systému firmy. Následovat budou doporučení, návrhy na zlepšení a úvahy nad možnými riziky, která jsou spojena s výběrem nového informačního systému firmy.

The master's thesis deals with the assessment of the current information system in a company, which does not want to disclose its trade name. It will be referred to as ČTKH. Assessing of the company's information system will be based on the results of two questionnaires. The output of the surveys will be to evaluation of the current information system in the company. Further on there will be recommendations, suggestion for improvement and consideration of the possible risks which are associated with the selection of a new information system company.
Information System Assessment and Proposal for ICT Modification
Keywords: Informační systém; bezpečnost informačního systému; pravidla; přístupy a rizika s daty; úroveň řízení a podpory.; Information system; security of information system; rules; approaches and risks of date; a level of management and support.